Rasch Analysis of the General Life Skills Scale for Dating Violence Prevention in Indonesian Adolescents - Suci Musvita Ayu; Zahroh Shaluhiyah; Bagoes Widjanarko; Ani Purwanti (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Early life skills education has the potential to be an effective intervention in preventing adolescent dating violence (ADV). However, measurement tools for life skills in general in the context of ADV prevention are still limited. Objective: This study aims to evaluate the psychometric properties of the General Life Skills Scale (GLSS) using the Rasch model. Methods: This study is classified as research and development. A total of 366 junior high school students (111 students from private schools and 255 students from public schools) in Indonesia participated in the empirical validation of the General Life Skills Scale (GLSS). The GLSS consists of 48 items spread across the constructs of personal skills (22 items) and social skills (26 items). GLSS used a four-point Likert scale, from 1 (strongly disagree) to 4 (strongly agree). The psychometric properties of the GLSS were evaluated using Rasch modeling. The psychometric properties were reviewed based on reliability, item fit, unidimensionality, and item distribution at each level of difficulty. Results: The results of the analysis showed that the GLSS had excellent reliability (? = 0.96; person reliability = 0.93; item reliability = 0.95). The separation index showed the scale's ability to distinguish respondents in five ability strata and items in six difficulty levels. Of the 48 items, 26 items met the Rasch model fit criteria, and unidimensionality analysis confirmed that the scale measured one main construct. However, the Wright map showed logit gaps between items, especially at the very easy difficulty level. Conclusion: The GLSS is considered valid and reliable for measuring adolescents' life skills in the context of preventing dating violence; however, improvements in item distribution are recommended to enhance measurement accuracy. Theoretically, this study contributes to the development of a general life skills scale in adolescent development theory. Practically, this study provides a validated scale for educators to design life skills curricula and can be integrated into school-based ADV prevention programs.